4U 1608–52 as a quasi-persistent X-ray source. (9th November 2020) - Šimon, Vojtěch
Abstract: 4U 1608–52 is a soft X-ray transient. The analysis presented here of a particular part of its X-ray activity uses observations of RXTE/ASM and Swift/BAT. We show a time segment (MJD 54262–MJD 55090) (828 d) in which 4U 1608–52 behaved as a quasi-persistent X-ray source with a series of bumps, with a complicated relation between the evolution of fluxes in the soft (1.5–12 keV) and the hard (15–50 keV) X-ray regions. We ascribe these bumps to a series of propagations of heating and cooling fronts over the inner disk region without any transitions to the true quiescence. 4U 1608–52 oscillated around the boundary between the dominance of the Comptonized component and the dominance of the multicolor accretion disk in its luminosity. Only some of the bumps in this series were accompanied by a transition from the hard to the soft state; if it occurred, it displayed a strong hysteresis effect. The hard-band emission with the dominant Comptonized component was present for most of this active state and showed a cycle of about 40 d. We argue that the cyclic variations of flux come from the inner disk region, not, e.g., from a jet. We also discuss the observed behavior of 4U 1608–52 in the context of other quasi-persistent low-mass X-ray binaries.